Happy for no reason 7 steps to being happy from the inside out - Shimoff, Marci; Kline, Carol (Free Press, 2008)
Everyone wants to be happy--yet so many people are unhappy today. What are they doing wrong? Clearly, a new approach is needed. No matter what happens to a person, they will tend to return to a set range of happiness. This book shows how you can actually reprogram your set-point to a higher level.